CompTIA CySA+ study guide Exam CS0-003 - Chapple, Mike 1975-; Seidl, David (Ascent Audio, 2024)
In the newly revised third edition of CompTIA CySA+ Study Guide: Exam CS0-003, a team of leading security experts and tech educators delivers comprehensive and accurate coverage of every topic and domain covered on the certification exam. You'll find clear and concise information on critical security topics presented by way of practical, real-world examples, chapter reviews, and exam highlights. Prepare for the test and for a new role in cybersecurity with the book's useful study tools, including: hands-on lab exercises and an opportunity to create your own cybersecurity toolkit; authoritative discussions of each exam competency, including security operations, vulnerability management, incident response and management, and reporting and communication; and complimentary access to Wiley's proven library of digital resources, including an online test bank, bonus questions, flashcards, glossary, and more. Reduce test anxiety and get a head-start learning the on-the-job skills you'll need on your first day in a cybersecurity career. Or augment your existing CompTIA Security+ certification with an impressive new credential. Fully updated for the newly released CS0-003 exam, CompTIA CySA+ Study Guide: Exam CS0-003, Third Edition is an essential resource for test takers and cybersecurity professionals alike.
Online resource; title from title details screen (O'Reilly, viewed January 17, 2024)
Keywords: Computing Technology Industry Association -- Study guides -- Examinations; Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Audiobooks; Livres audio